Analisis Fiqih Muamalah Terhadap Transaksi Jual Beli Online Pada Platform Shopee - Tirta Ahmad Zamharir; Bilqis Naila Azzahro (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Currently, the internet has a big influence on the development of businesses that are already running. Business is growing rapidly through online media buying and selling transaction activities known as online shopping. In this research, the type of research used is library research. This research was carried out by exploring various literature related to the concept of online buying and selling from the perspective of muamalah fiqh. This aims to provide a comprehensive explanation of social media-based online buying and selling which is currently popular along with the development of technology and the internet. The contents of the research results show that online buying and selling transactions are generally acceptable within the framework of muamalah fiqh, as long as they fulfill the conditions stipulated by Islamic law. One of the important findings in online buying and selling transactions is often the greeting contract, where the buyer orders goods based on the description given by the seller. The practice of online buying and selling can be accepted from the perspective of muamalah fiqh if it meets the requirements of a valid contract, clarity of goods, and the principle of transparency. Understanding legal aspects, both sharia and positive, is necessary so that this practice runs in accordance with Islamic principles and provides justice for all parties.